The effect of a commercial exogenous emulsifier supplementation on growth performance, nutrient digestibility and serum lipid profilein broiler chickens - Tan, Hui San; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Goh, Yong Meng; Croes, Evi; Partha, Sarathi Karmakar; Tee, Ah Kiat (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The research was to evaluate the effect of a commercial exogenous emulsifier, Volamel, supplementation to broiler chicken diets on growth performance, digestibility of fat and apparent metabolizable energy (AME) content and serum lipid profile during week 1, 2, 3 and 5.A total of 360 one-day-old male Cobb broiler chicks were assigned in groups of 30 to 12 battery cages. The chicks were randomly assigned to two dietary treatments, with 6 replicate cages per treatment. The diets were either standard broiler starter (3035 kcal ME/kg and 21% crude protein) and finisher (3180 kcal ME/kg and 18% crude protein) (control) or similar diets + 0.05% Volamel (VO). From week 2 till 5, feed intakes of VO chicks were reported significantly reduced when compared to those of untreated birds. The control birds had significantly greater body weights than those of VO on week 1 but the converse was noted on week 2. Both groups of birds had similar body weights on week 3 onwards. Except for week 2, supplementation with Volamel significantly improved FCR when compared to the control group. Addition of emulsifier showed higher AME than controls at week 1, 3 and 5. Fat digestibility on week 1 and 2 was also improved in VO birds when compared to their control counterparts. Dietary supplementation with Volamel resulted in significantly higher serum levels of cholesterol and HDL-cholesterol but no significant difference intriglycerides and LDL-cholesterol. In conclusion, supplementing Volamel into broiler diet can improve AME, fat digestibility, and FCR. Volamel supplementation was also effective in increasing serum HDL-cholesterol and reducing serum triglycerides. Thus, Volamel is a beneficial dietary supplement for broiler chickens.